(3GdSQ GdeSJHGf eeG ChOYg Gddg ef GdNhGU aj CLRGA GdMjhGfs - (3CMeO Hf YeGO Hf jhSa Hf YHO GdfHi CHh GdYHGSs; (3GdOejQj , ceGd GdOjf CHh GdHbGA eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj, GdOejQj,J (B808 (3g` s
(3ChdgG (B:s
(3CeG HYO aCbhd hHGddg GdJhajb gPG JdNjU ai eYQaI Led ef GdNhGU eSJNQL ef cJGH MjGI GdMjhGf ddOejQi s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B65 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B178s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B114 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B64 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs